Postscript: In pursuit of integration. (October 2018) - List, Alexandra; Alexander, Patricia A.
Abstract: In this conclusion to the Special Issue, features of multiple documents and multi-modal documents are systematized. Specifically, documents are defined according to their (a) intended message, (b) author and purpose for being created, (c) symbol system(s) used, and (d) related nature. Indeed, documents are conceptualized as presenting complementary content across symbol systems (i.e., multi-modal documents) or as presenting information on a common topic across multiple texts (i.e., multiple documents). Processes associated with each of these document features (i.e., encoding, comprehension, evaluation, and relation/integration) are specified. Finally, articles included as a part of this Special Issue are conceptualized according to the features and processing of multiple documents and multi-modal documents that they exemplify. The aim of this postscript is to move the field toward a model of multiple, multi-modal document comprehension and integration. Highlights: Multiple documents and multi-modal documents are defined. Four features of multiple and multi-modal documents are identified (e.g., intended message, symbol system used). Four processes associated with multiple and multi-modal document processing are specified (e.g., encoding, integration). Papers in the Special Issue are conceptualized in terms of the document features and processes exemplified.